Kufa and its political role - Mizel, Iman Kadhim (Al-Adab Journal, 2015)
Kufa history the great city was Muslim second, which was established in Iraq after the Arab conquest, and had since its inception home of the Arab Mujahideen and the Centre for Islamic power, was known Kufa sympathetically military because they are the headquarters of the State Commission, one of the most important Islamic capitals, and have had an impact in the political history and civilization, and it has the status of an important strategy in politics with its leadership and the site, has been a stronghold of supporters of the people of the house, and the Dome of Islam and Dar Muslim immigration and inhabited by the large size of the companions and followers and followers of followers and scholars and righteous people, and the princes, governors and poets, which is the cradle of jurists and legislators of the ancients, it was a center for life science and cultural activities, and for what left us from the effects of literary and scientific unforgettable Over a lifetime, the city has been unable to compete in the first century (sixth century), only the city of Basra (). We have grown this city and Thoudrt and many where urbanization and reached the height of its power in the Umayyad period, he participated army post effective in open large parts of Persia (), and after operations Open Anzmt provinces rich to the Islamic state, and they generate income and a lot of money, thereby increasing importance, saw Kufa events and political developments and disturbances are many important, the martyred Imam Ali bin Abi Talib (peace be upon him) and Azaajoh close to her, and she was also a center of intrigue and fraud, and passed the roles contradictory are among the roles of the Islamic empire, and suffered wars and accidents amazing (). The historians draw a picture of Kufa represent fluctuations that got in. Osmoha nature and amount of hypocrisy and betrayal and the oscillation frequency. The task of searching tedious and difficult for any scientific researcher because it requires precision in the introduction of sources of objectivity in scientific writing and focus on the question of the truth and nothing else, and systematically in this research is based on the facts after the classification and selection, with the graduation of novels from sources Biography For the sequence of events and connectivity, said details of the proceedings according to the chronology and punish the years and figures contained translation and definition contained areas also.